Optimizing pain management and pupil dilation in cataract surgery: a systematic review and meta-analysis of phenylephrine/ketorolac (OMIDRIA®) - Mohamed Abo Zeid (20020680) (2025)
Purpose This systematic review and meta-analysis aims to evaluate the efficacy and safety of the combination of phenylephrine 1% and ketorolac 0.3% (OMIDRIA®) for optimizing pain management and maintaining pupil dilation during cataract surgery. Comparisons were made against placebo/vehicle, phenylephrine alone, and epinephrine. Methods A comprehensive search of PubMed, Cochrane CENTRAL, Embase, Scopus, and Web of Science was conducted. Eligible studies were randomized clinical trials and observational studies assessing intracameral phenylephrine/ketorolac against control groups. Key outcomes included pain management, pupil diameter, and adverse events. Data were synthesized using meta-analysis with fixed and random-effects models, and heterogeneity was assessed using the I2 statistic. Results Ten studies, including 220,061 patients, were analyzed. The combination of phenylephrine/ketorolac significantly reduced postoperative pain (RR = 0.72, 95% CI: 0.60–0.86) and opioid use (RR = 0.45, 95% CI: 0.23–0.89) compared to vehicle and epinephrine. PE/K also maintained a larger pupil diameter (MD = 0.54 mm, 95% CI: 0.32–0.75) with minimal heterogeneity (I2 = 0%) and reduced the incidence of severe pain (RR = 0.41, 95% CI: 0.27–0.63). No significant differences in adverse events such as elevated intraocular pressure, inflammation, or headaches were observed. Conclusion Phenylephrine/ketorolac (OMIDRIA®) demonstrates superior efficacy in maintaining intraoperative mydriasis, reducing postoperative pain, and minimizing opioid use without increasing adverse events. This combination offers a preferable alternative to traditional agents, potentially setting a new standard for pain management and pupil dilation in cataract surgery. Other Information Published in: Graefe's Archive for Clinical and Experimental Ophthalmology License: https://creativecommons.org/licenses/by/4.0 See article on publisher's website: https://dx.doi.org/10.1007/s00417-025-06811-y